Analisis Risiko Tsunami Berbasis GIS dan Kondisi Eksisting Pantai untuk Mitigasi Bencana di Kota Banda Aceh - Laela Rustiani; Bambang Agus Herlambang; Ahmad Khoirul Anam (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Banda Aceh City has high vulnerability to tsunamis due to its coastal location directly facing the sea and being situated in an active tectonic zone. This study evaluates the spatial distribution of tsunami risk and assesses coastal conditions as disaster mitigation efforts using a mixed-method approach that combines quantitative analysis based on Geographic Information Systems (GIS) and qualitative analysis through field surveys and expert assessments. Three beaches were selected as study locations: Ulee Lheue Beach, Syiah Kuala Beach, and Alue Naga Beach, with risk assessment calculated using the formula Risk = (H × V) / C according to the BNPB framework and overlay techniques in GIS to create risk distribution maps. Coastal condition evaluation focused on coastal vegetation and protective coastal structures assessed using an ordinal scale of 1–5. Results show that Ulee Lheue Beach has the highest mitigation capacity with a score of 64.5% (good category), Syiah Kuala Beach reaches 57.5% (fairly good), while Alue Naga Beach has the lowest score of 28.3% (poor). Correlation analysis yielded a coefficient of r = 0.97, indicating a very strong positive relationship between coastal vegetation and protective coastal structures. Therefore, the study recommends strengthening mitigation strategies through improved protective infrastructure and optimization of coastal vegetation functions, particularly in high-risk areas, to reduce tsunami impacts in the future.